The Influence of Store Atmosphere, Location and Price on Repurchase Intention (Case Study on the Costumer of Carrefour DP Mall Semarang) - Sarahnadia Sarahnadia; Sri Suryoko (Jurnal Ilmu Administrasi Bisnis, 2017)
The number of retail markets in Semarang which getting larger lead into business completion among them. It made the costumer has many choices to change their preference in choosing the retail markets. Carrefour is one of modern retail markets in Semarang which categorize as hypermarket. Because of many business competitors which had more decent atmosphere, more strategic area, and cheaper price the amount sales in Carrefour was decrease in line with the rate of costumer debit in 2014-2016.The objective of this study was to discove the influence of store atmosphere, location and price on the repurchase intention of the costumer Carrefour DP Mall Semarang. This study is an explanatory research. The method of data collection used in this study was accidental sampling. There are 100 respondents as the sample of this research. The data was analyzed through validity test, reliability test, crosstab, correlation coefficient, determination coefficient, simple linier regrestion, double linier regrestion, t test, F test by using IBM SPSS version 16.0.Based on the analyzed result, it can be concluded that there was a significant positive influence among store atmosphere, location and price on costumer repurchase intention partially and simultaneously. The suggestion which could be give to the Carrefour DP Mall Semarang is to redesign the display and the decoration inside the shop to be more attractive and considering the Price of some ítems which might be higher tan the competitor.